Fabrication of Hydrogel Beads Based on Mesoporous Silica Nanoparticles/Chitosan and Application as a Slow-Release Fertilizer - My Chau Phan; Hoang Thanh Han Tran; Ngoc Nhu Y Ha; Vu Hoang Giang Phan; Van Quy Nguyen (Journal of Technical Education Science, 2024)
Hydrogels have gained significant attention in various applications, including agriculture, owing to their exclusive characteristics, such as great water retention and controlled delivery of fertilizers and agrochemicals. In this study, a nanocomposite hydrogel bead with exceptional slow-release capacity for urea fertilizer has been fabricated by appropriately combining urea, silica nanoparticles, and chitosan. The developed beads not only enable the efficient delivery of nutrients to plants over a long period but also enhance water retention capacity in sandy soil, resulting in minimally negative impacts on the environment. The hydrogel beads were simply prepared by dropping method. To effectively control the release of urea from hydrogel beads, mesoporous silica nanoparticles (MSNs) with a diameter of 56 nm were synthesized and used to load the urea (UM). Subsequently, the UM hybrid was incorporated into the chitosan matrix to form the hydrogel beads (UMCS). The resulting beads have a spherical shape and high stability. They exhibited a sustained release of urea for over a month and biodegradable capacity in soil. The hydrogel beads showed a good swelling degree with a maximum value of 250% at pH 3. Moreover, the hydrogel beads-embedded soil revealed a water retention capacity significantly greater than the soil without the beads. These results suggested that the nanocomposite hydrogel beads possess high application potential in fertilizer delivery and smart agriculture.